The effect of TAM factor on behavioral intention to use (dashboard property management Ciputra SH3A) - Chandra, Amelia; Hermeindito, Hermeindito (Enrichment : Journal of Management, 2024)
This study aims to determine the influence between variables on the role of technology utilization in the use of property management dashboards with the Technology Acceptance Model (TAM) Factor theory approach introduced by Davis (1989) on the influence of perceived usefulness, perceived ease of use, and trust of security to see how user intention (behavioral intention to use) influences the use of property management dashboards at Ciputra SH3A as actual system use. This type of research is quantitative research using SmartPLS 3.0 software and data collection techniques in research through online questionnaires on a saturated sample of 60 respondents who are all users of the property management dashboard with a Likert scale range of 5. The results of this study indicate that all independent variables (perceived usefulness, perceived ease of use and trust of security) have a significant positive effect on the dependent variable (behavioral intention to use), where the variable perceived ease of use has the greatest effect on behavioral intention to use in using the property management dashboard at Ciputra SH3A